Users and non-users in engineering and feminist participatory research on sustainable aviation - Stilke, Julia; Buchmüller, Sandra (NOvation — Critical Studies of Innovation, 2022)
Within engineering, economics, and the natural sciences, sustainable aviation is often configured as an ecological and economic problem, which can be solved through technological innovation. In contrast to this, we set up a research project centering on social innovation, named Human demands of sustainable aviation. In the project, we combined theories from Feminist Science and Technology Studies (FSTS) with methods from Participatory Design (PD) and practice-based Ontological Design (OD). In this paper, we use our project as a case study to analyze and discuss how users and non-users are configured within different disciplinary contexts. The findings illustrate that conceptualizations and categorizations of users and non-users are not stable. They denote highly situated phenomena that emerge out of different research approaches and understandings of innovation. Power structures that are entangled with the positions researchers take, including specific theories, methods, and (implicit) values, pervade these contexts and understandings. With this in mind, we advocate for power-critical reflections on the performative effects of knowledge making as processes of world making and for inter- and transdisciplinary research to do justice to the different life worlds we inhabit. We further argue that innovation should be based on collectively negotiated visions of how we want to live in the future, instead of predictions that project our current realities into the status quo of tomorrow.